EFEKTIVITAS MEDIA VISUAL UNTUK MENINGKATKAN KETERAMPILAN MENGHIAS TEMPAT AIR MINERAL BAGI ANAK TUNARUNGU KELAS IX SMPLB YPPLB PADANG - Sri Riska Ade Permana Sari (Universitas Negeri Padang, 2015)
Abstract :This reseacrh was motivated by the problems that the researcher found in class IX deaf children SMPLB YPPLB Padang. The children did not know how to decorate the place of dringking bottle in accordance with the steps. The design of this reseach was A-B-A design and data analysis techniques was visual analysis chart. The subject for this research was the deaf childrens, the assessment in this research was percentages that was to calculate the childrens’ ability to decorate the place of dringking bottle. Based on the results of the research, the ability of children in decorating the place of dringking bottle increased through visual media. At baseline condition (A1) was done in five meetings, the ability of the children was 25%. On the intervention condition (B) was done in nine meetings, the children ability increased to 94,44%. At the baseline condition (A2) the ability of children was 94,44%. From the analysis of the data showed that the result change tended to increase (+), from baseline condition (A1) to intervene and baseline (A2) percentage overlape small data that was 44,44% thus illustrate the effect of the intervention through visual media was increasing in the ability to decorate the bottle of mineral water for the deaf children. The hypothesis of this research is accepted. It can be concluded that the visual media can increase the skills in decorating the place of dringking bottle for the deaf children at Grade IX SMPLB YPPLB Padang. Researcher suggests to the teachers and the next researchers to make the results of this reseacrh as a reference in developmenting of learning skills at school. Key Words : Keterampilan ; Menghias ; Tempat Air Mineral ; Media Visual